2014
DOI: 10.1007/s10853-014-8488-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of gravity in the crystallization suppression of ZBLAN glass

Abstract: Lauren Hunt. I have the privilege and honor of calling each of them my friend. I would also like to thank my supervisor at Applied Technology Associates, Johnathan Jones. This entire process wouldn't have operated as smoothly without Johnathan's efforts. This research was funded by the Air Force Research Laboratory Space Vehicles Directorate (AFRL/RV). I want to thank them for the invaluable contributions and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Early microgravity experiments on ZBLAN suggested that crystallization may be suppressed in reduced gravity 12 , thereby widening the working temperature range and hypothetically making it possible to manufacture higher-quality ZBLAN fiber. The increase in crystallization temperature was speculated to arise from a lack of buoyancy-driven convection 13 , though a full mechanistic explanation remains lacking. Nonetheless, multiple commercial efforts are currently pursuing space-based processing of ZBLAN fibers 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Early microgravity experiments on ZBLAN suggested that crystallization may be suppressed in reduced gravity 12 , thereby widening the working temperature range and hypothetically making it possible to manufacture higher-quality ZBLAN fiber. The increase in crystallization temperature was speculated to arise from a lack of buoyancy-driven convection 13 , though a full mechanistic explanation remains lacking. Nonetheless, multiple commercial efforts are currently pursuing space-based processing of ZBLAN fibers 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%